2006
DOI: 10.1016/j.respol.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Faculty support for the objectives of university–industry relations versus degree of R&D cooperation: The importance of regional absorptive capacity

Abstract: The growing importance of regions in the analysis of innovation and the pressure on European universities to interact with their environment justify this article. It argues that faculty support for the objectives of university-industry relations (UIR) does not vary across disciplines and does not respond to university encouragement in a region with low absorptive capacity. These results are in contrast with those obtained in studies of technology leading countries like the USA. Furthermore, incentives for UIR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0
9

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(83 citation statements)
references
References 25 publications
3
71
0
9
Order By: Relevance
“…Universities and research institutions in particular are accumulators of specific knowledge, and firms that work together with universities can improve their knowledge base and thereby increase their innovation performance. More specifically, various studies have shown that, when they work together with universities, SMEs can benefit from increasing their access to useful knowledge and skilled graduates and increase their technological problem-solving capacity (Cohen and Levinthal, 1990;Salter and Martin, 2001;Azagra-Caro et al, 2006;Kodama, 2008) and innovative capability (Kaufmann and Tödtling, 2001;Balconi and Laboranti, 2006). Although these studies suggest that having an innovation-based strategy and being linked to universities will improve firm performance, other researchers found inconclusive evidence with regard to the existence of such a causal connection (for example, Capon et al, 1990;Lee et al, 2001;Song et al, 2008), which may be due to the complex, systemic, context-related, tacit and non-codified nature of innovation (Autio, 1997) and of the knowledge that is transferred from universities to SMEs (Agrawal, 2006), which often requires more detail than can be obtained through traditional publications such as conferences, journals and patents (Mowery et al, 1996;Almeida and Kogut, 1999;Owen-Smith and Powell, 2003).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Universities and research institutions in particular are accumulators of specific knowledge, and firms that work together with universities can improve their knowledge base and thereby increase their innovation performance. More specifically, various studies have shown that, when they work together with universities, SMEs can benefit from increasing their access to useful knowledge and skilled graduates and increase their technological problem-solving capacity (Cohen and Levinthal, 1990;Salter and Martin, 2001;Azagra-Caro et al, 2006;Kodama, 2008) and innovative capability (Kaufmann and Tödtling, 2001;Balconi and Laboranti, 2006). Although these studies suggest that having an innovation-based strategy and being linked to universities will improve firm performance, other researchers found inconclusive evidence with regard to the existence of such a causal connection (for example, Capon et al, 1990;Lee et al, 2001;Song et al, 2008), which may be due to the complex, systemic, context-related, tacit and non-codified nature of innovation (Autio, 1997) and of the knowledge that is transferred from universities to SMEs (Agrawal, 2006), which often requires more detail than can be obtained through traditional publications such as conferences, journals and patents (Mowery et al, 1996;Almeida and Kogut, 1999;Owen-Smith and Powell, 2003).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…However, the exact ways by which this is to be achieved in universities that have traditionally lacked formal linkages with industry are still unclear. International literature indicates that the UITT process is highly context-dependent, with the required policies and instruments differing by institution and also according to the size, structure, and absorptive capacity of the economic system it appeals to (Azagra-Caro et al, 2006;Lee and Win, 2004;Lee, 2000;Siegel et al, 2003a, b). Other international studies have shown that established traditions and informal procedures may jeopardise the effective introduction of formal UITT instruments such as TTOs (see Kneller (1999) for evidence from Japan).…”
Section: Theoretical Rationalementioning
confidence: 99%
“…Second, scientific productivity appears to go handin-hand with patented industrial applications by university researchers (Meyer, 2006;Wong and Singh, 2009). Third, excellent universities in regions with low absorptive capacity may cooperate with firms from other territories (Azagra-Caro et al, 2006) in the search for advanced technological standards (Azagra-Caro, 2007). In these other regions with higher absorptive capacity, proximity may be enough for cooperation among local actors (Castro et al, 2008), so firms will benefit from universities within and outside the region, reinforcing their previously winning position.…”
mentioning
confidence: 99%